2017
DOI: 10.1002/arcp.1008
|View full text |Cite
|
Sign up to set email alerts
|

Health decision making

Abstract: Health decision making has become a fundamental part of everyday consumer life. In the relatively simple course of making a meal choice, planning a trip to the gym, or forgetting to pick up a prescription, consumers' routine choices will cumulatively define their health. In this article, we will explore the marketplace forces that shape health decisions by drawing on classic and contemporary research from marketing, psychology, and health. K E Y W O R D Sconsumer health behavior, goal activation, self-control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 143 publications
(161 reference statements)
0
3
0
2
Order By: Relevance
“…Increasing healthcare literacy and combatting misinformation were also important goals. Achieving these goals would ensure health-conscious behaviours are sustained and assist with future infection control and minimization of healthcare system burden [ 6 ]. Healthcare literacy was promoted throughout the community by the use of social and traditional media platforms with consistent and evidence-based information.…”
Section: Maintaining Control Over the Covid-19 Pandemicmentioning
confidence: 99%
“…Increasing healthcare literacy and combatting misinformation were also important goals. Achieving these goals would ensure health-conscious behaviours are sustained and assist with future infection control and minimization of healthcare system burden [ 6 ]. Healthcare literacy was promoted throughout the community by the use of social and traditional media platforms with consistent and evidence-based information.…”
Section: Maintaining Control Over the Covid-19 Pandemicmentioning
confidence: 99%
“…Consequently, understanding the causes of self‐control provides an avenue for developing strategies that foster self‐control successes and reduce self‐control failures. The importance of helping people exert self‐control explains the proliferation of self‐control research over the past decade (Wang, Bendle, Mai, & Cotte, ), which has identified a number of factors that lead consumers to exert self‐control or indulge (Klesse, Levav, & Goukens, ; Laran, Janiszewski, & Salerno, ; Schwartz, ; Shen, Zhang, & Krishna, ). Examples include consumers' emotions (Salerno, Laran, & Janiszewski, ), goals (Ülkümen & Cheema, ), resource availability (Cannon, Goldsmith, & Roux, ), and individual characteristics (Laran & Janiszewski, ; Tangney, Baumeister, & Boone, ).…”
Section: Introductionmentioning
confidence: 99%
“…La sensibilidad a las sustancias químicas que estimulan a los receptores del gusto está determinada por factores genéticos y por la exposición de los individuos a las sustancias existentes en la dieta diaria. Por esta razón, la participación de los padres en la introducción de una amplia variedad de alimentos y experiencias de alimentación rica y saludable es relevante para permitir la exposición y, en consecuencia, generar aceptación para el consumo de dietas saludables (Schwartz, 2018). Kobayashi & Kennedy (2002) informaron que los japoneses deberían ser capaces de detectar la presencia de GMS más fácilmente, que un grupo de americanos e/o europeos expuestos al GMS en la dieta, en comparación con otro grupo que no estaba expuesto al estímulo.…”
Section: Aspectos Sensoriales Del Umamiunclassified